The Implementation of Short Story in Enhancing Student’s Vocabularies - Nabila Myrrha Rahmawati (Wanastra: Jurnal Bahasa dan Sastra, 2020)
Literary works have attracted more attention as a pedagogical instrument in enhancing vocabulary in recent years. Short stories refer to the learning media that is applied by the teacher to help the student in improving student’s vocabulary based on the context of reading a certain text. The Increased interest in a student-centered approach makes this short story received attention from a variety of studies. In the case of students must be more active in the learning process.The activity lets the students explore various new words, the content of the story and also sentence structure. The focus of the activity is to define and understand the words in a specific context based on the content of the text. This paper is a literature review from a previous study of short stories in English as a Second / Foreign Language context (ESL / EFL). The ten short story studies from the last ten years were widely reviewed and systematically analyzed. A short story from the study reviewed is about the quality of student vocabulary results in the context of EFL / ESL due to understanding vocabulary plays an important role in learning English. As a critical review paper of these studies, this paper highlights the obstacles faced during a teaching in improving vocabulary and the practicality of short stories as an effective pedagogical instrument in improving vocabulary. This study hopes that it can be useful and used effectively by educators in the ESL and EFL classrooms in the future. Keywords: Short Story, vocabulary learning, learning and teaching activity